An extremely rare coexistence of achalasia cardia with esophageal leiomyoma: An endoscopic treatment approach - Pankaj Desai; Chintan Patel; Mayank Kabrawala; Subhash Nandwani; Rajiv Mehta; Ritesh Prajapati; Nisharg Patel; Krishna Parekh (Society of Gastrointestinal Intervention, 2020)
The coexistence of an esophageal leiomyoma with an achalasia cardia is extremely rare and poses a diagnostic dilemma as the clinical presentation of an esophageal leiomyoma strongly resembles to an achalasia cardia. Moreover, at most of the time, an esophageal leiomyoma exist with absence of leiomyoma specific symptoms or findings. It could be the reason why the diagnosis of esophageal leiomyoma is missed while the patient has the coexistence of the both. Here, we present a case series of an unusual coexistence of an esophageal leiomyoma with achalasia in three patients who were presented with dysphagia and had an initial diagnosis of achalasia. Even endoscopic evaluation couldn't reveal esophageal leiomyoma; it became apparent during the peroral endoscopic myotomy.